The HIV-1 Gp120/CXCR4 Axis Promotes CCR7 Ligand-Dependent CD4 T Cell Migration: CCR7 Homo- and CCR7/CXCR4 Hetero-Oligomer Formation as a Possible Mechanism for Up-Regulation of Functional CCR7 - Hayasaka H; Kobayashi D; Yoshimura H; Nakayama EE; Shioda T; Miyasaka M (PUBLIC LIBRARY SCIENCE, 2022)
During human immunodeficiency virus (HIV) infection, enhanced migration of infected cells to lymph nodes leads to efficient propagation of HIV-1. The selective chemokine receptors, including CXCR4 and CCR7, may play a role in this process, yet the viral factors regulating chemokine-dependent T cell migration remain relatively unclear. The functional cooperation between the CXCR4 ligand chemokine CXCL12 and the CCR7 ligand chemokines CCL19 and CCL21 enhances CCR7-dependent T cell motility in vitro as well as cell trafficking into the lymph nodes in vivo. In this study, we report that a recombinant form of a viral CXCR4 ligand, X4-tropic HIV-1 gp120, enhanced the CD4 T cell response to CCR7 ligands in a manner dependent on CXCR4 and CD4, and that this effect was recapitulated by HIV-1 virions. HIV-1 gp120 significantly enhanced CCR7-dependent CD4 T cell migration from the footpad of mice to the draining lymph nodes in in vivo transfer experiments. We also demonstrated that CXCR4 expression is required for stable CCR7 expression on the CD4 T cell surface, whereas CXCR4 signaling facilitated CCR7 ligand binding to the cell surface and increased the level of CCR7 homo-as well as CXCR4/CCR7 hetero-oligomers without affecting CCR7 expression levels. Our findings indicate that HIV-evoked CXCR4 signaling promotes CCR7-dependent CD4 T cell migration by up-regulating CCR7 function, which is likely to be induced by increased formation of CCR7 homo-and CXCR4/CCR7 hetero-oligomers on the surface of CD4 T cells.